Reseña de ONU, The United Nations and the Advancement of Women 1945-1995 - Covián G., Miguel Ángel (Revista Mexicana de Política Exterior, 2022)
ONU, The United Nations and the Advancement of Women 1945-1995, Nueva York, ONU, (The United Nations Blue Book Series, vol. VI), 1995, 689 pp.